Un modele de gauchissement pour les plaques piezo-electriques - Hassis, Hedi; Pidaparti, Ramana (European Journal of Computational Mechanics, 2000)
A warping theory for the piezoelectric composite plates is presented using a previously developed model for laminated composite plates. The warping theory takes into account the effects of non linear distribution of the displacements through the thickness and also the transverse shear deformation. The results from the present theory are compared to the low-order theory of Mindlin and exact solutions available in the literature. Examples of a one layer and two layer composite plates were presented to illustrate the thickness effects on displacements, stresses and electric potential. The results obtained indicate that warping theory gives more realistic predictions as compared to lower order theories of piezoelectric composite plates.